The Synergy Between Industry 4.0 and Circular Economy for Sustainable Performance in the Libyan Manufacturing Industry - Najat Omran (المجلة الأفروآسيوية للبحث العلمي, 2025)
This study explores the evolving landscape of the manufacturing sector, which faces increasing pressure to achieve sustainability amidst resource scarcity and rapid technological advancements. Industry 4.0 (I4) technologies offer solutions to optimize resource utilization and productivity, while the Circular Economy (CE) paradigm addresses environmental regulations, resource price volatility, and supply chain uncertainties. Despite their individual contributions, the synergistic relationship between I4 technologies, CE practices, and their combined impact on Sustainable Performance (SP) remains underexplored, particularly within the Libyan manufacturing industry. This research aims to address this gap through an empirical investigation. Data were collected from 110 Libyan manufacturing organizations via a questionnaire-based survey. The Statistical Package for the Social Sciences (SPSS) software was utilized for data analysis. The findings are expected to provide conceptual and empirical insights into how I4 technologies facilitate the transition towards CE practices and their joint impact on sustainable performance, identifying key drivers, enablers, and barriers within this context.